Pure dip-slip along the Tuz Gölü Fault Zone accommodates east-west extension of Central Anatolia - Gençoğlu Korkmaz, Gülin; Harvey, Janet C.; Danišik, Martin; Schoenbohm, Lindsay M.; Schmitt, Axel Karl (Communications earth & environment, 2025)
Kinematic constraints on faults with slow slip rates often diverge, obscuring their neotectonic significance and seismic hazards. The Tuz Gölü Fault Zone (TGFZ) is a major slow-moving fault accommodating intraplate deformation within Central Anatolia, for which long-term geological and short-term geodetic deformation rates disagree. Here, the Pleistocene-Recent kinematic evolution of the TGFZ is determined by dating dissected lava flows of the Hasandağ stratocone. Combined zircon U-Th and (U-Th)/He ages indicate emplacement between 151 ± 6 ka and 38.8 ± 2.0 ka (2σ uncertainties). Restoring flow levees as tie points across fault scarps yields vertical displacement rates of 0.90 ± 0.06 to 1.23 ± 0.08 mm/a for the most reliable projections, whereas in contrast to previous notions only negligible dextral strike slip at 0.01 ± 0.08 to 0.06 ± 0.08 mm/a is permitted. Predominantly normal faulting without a major strike-slip component for the TGFZ supports ongoing east-west extension without the requirement for shearing due to north-south shortening of Central Anatolia between its bounding megashears as it gradually escapes westward.